Emotional labour: a case of fast food employees in Klang Valley, Malaysia - Ghazali, Hazrina; Yap; Ahmad (Universiti Teknologi MARA, 2014)
This study aims to investigate the level of agreement on emotional labour strategies that include standard scripts, dress code and acting and the roles of socio-demographic towards emotion supervision of fast food employees. A survey questionnaire was used to underpin this study with participation of 170 respondents among fast food employees in Klang Valley area. Data were analysed by using SPSS version 19 and the results found that the use of standard scripts, dress code and acting had from moderate to high level of agreement on employees’ emotion. This study was hoped to give information and deeper insights about emotional labour. Managers can take an initiative to guide employees in order to provide good services and smooth interaction between employees and customers where it benefited both parties.